Physicochemical Content, Metabolizable Energy and In-vitro Protein Digestibility of Wheat Screening Diet on Growth Rate of Broiler - Saki, A.A.; Alipana, A. (International Journal of Poultry Science, 2004)
In competitions by monogastric animal particular in poultry by consumption human food sources, high attempt should be made to find out new sources of feed that is not consumed by human. Wheat screening is one of the these sources of feed which need to be considered. Determination of physicochemical content, metabolizable energy (ME) and protein digestibility may lead to elucidate the quality of this feed as well as arrangement in feed formulation of broiler ration. Physical content of two types of wheat screening (W. S.) were tested by seed sorting system (grad 1 and 2), lots of straw, sand, dust, soil and none cereal seed were observed in wheat screening grads 2 compared with wheat screening grade 1. In addition 80% of wheat screening includes wheat screening grads 1 which content less Straw, soil, sand and none cereal seed. Otherwise metabolizable energy which was estimated by Sibbaled method was significantly higher (P